Validated UPLC‐MS/MS method for quantification of seven compounds in rat plasma and tissues: Application to pharmacokinetic and tissue distribution studies in rats after oral administration of extract of Eclipta prostrata L. (27th February 2018) - Du, Guangyan; Fu, Lingling; Jia, Jun; Pang, Xu; Yu, Haiyang; Zhang, Youcai; Fan, Guanwei; Gao, Xiumei; Han, Lifeng
Abstract: A rapid, sensitive and specific ultra‐high‐performance liquid chromatography coupled with tandem mass spectrometry (UPLC‐MS/MS) method was developed to investigate the pharmacokinetics and tissue distribution of Eclipta prostrata extract. Rats were orally administrated the 70% ethanol extract of E. prostrata, and their plasma as well as various organs were collected. The concentrations of seven main compounds, ecliptasaponin IV, ecliptasaponin A, apigenin, 3′‐hydroxybiochanin A, luteolin, luteolin‐7‐ O ‐glucoside and wedelolactone, were quantified by UPLC‐MS/MS through multiple reactions monitoring method. The precisions (RSD) of the analytes were all <15.00%. The extraction recoveries ranged from 74.65 to 107.45% with RSD ≤ 15.36%. The matrix effects ranged from 78.00 to 118.06% with RSD ≤ 15.04%. To conclude, the present pharmacokinetic and tissue distribution studies provided useful information for the clinical usage of Eclipta prostrata L.